The first fossil Cydnidae (Hemiptera: Pentatomoidea) from the Late Mesozoic of China - Yao, Yunzhi; Cai, Wanzhi; Ren, Dong (Zootaxa, 2007)
Two new genera and two new species of fossil amnestine burrower bugs, Cilicydnus robustispinus gen. & sp. nov. and Orienicydnus hongi gen. & sp. nov., are described and illustrated. They were collected from the Late Mesozoic nonmarine sedimentary strata of Northeast China. This finding represents the first record of fossil cydnids from China. The fossil cydnid localities and the distribution of extant taxa are summarized in a map.